Design and synthesis of novel diamide derivatives of glycine as antihyperglycemic agents. Issue 15 (2nd August 2016) - Sharma, Radhika; Soman, Shubhangi S.
ABSTRACT: DPP-4 inhibition is one of the most extensively explored approaches for the management of type 2 diabetes (T2D). Most DPP-4 inhibitors in the market contain a proline mimetic active pharmacophore. Herein, we report the design, synthesis, and preliminary evaluation of a series of novel diamide derivatives of glycine, devoid of the proline mimic, for the treatment of T2D. As predicted from in silico studies, the diamide derivatives of glycine exhibited comparable DPP-4 inhibition with the standard as confirmed by the preliminary in vitro studies. Compound6b was found to be the most potent (IC50 94.82 nM) DPP-4 inhibitor among all the molecules synthesized in the series. GRAPHICAL ABSTRACT: